Light Water Reactors with Crushed Rock Thermal Storage for Industrial Heat and High-Value Electricity. (3rd April 2017) - Forsberg, C. W.; Curtis, D.; Stack, D.
Abstract: A crushed rock heat storage facility with storage capacities of gigawatt-hours is proposed to couple to light water reactors (LWRs) to enable base-load LWR operation with (1) variable electricity to the grid and heat to industry and (2) substantially higher revenue in deregulated electricity markets with significant solar or wind generation capacity. At times of low electricity prices, crushed rock is heated by hot air in a two-stage process. Air is initially heated by a steam-air heat exchanger using LWR steam and then with electric resistance heaters before circulating from the top to bottom of the crushed rock pile. Depending upon the design, peak rock temperatures can be from 250°C to 800°C. Heat is recovered by circulating air from the bottom to the top of the crushed rock pile with the hot air sent to industrial furnaces or thermal electric power plants. For industrial applications the hot air is a partial replacement for the burning of fossil fuels in industrial furnaces. Many of the challenges and questions associated with such a system are being addressed by (1) the development of the Red Leaf shale oil process, where crushed oil shale in 30-m-high piles is heated with hot gases to thermally decompose solid kerogen to produce a light crude oil, and (2) firebrick resistance-heated energy storage (FIRES), where low-price electricity is used to heat firebrick to provide stored heat for space heating and in the future may provide heat for electricity production or industrial heat.